2014
DOI: 10.5897/ijwree2013.0443
|View full text |Cite
|
Sign up to set email alerts
|

Determination of rainfall-recharge relationship in River Ona basin using soil moisture balance and water fluctuation methods

Abstract: A quantitative evaluation of spatial and temporal distribution of groundwater recharge is a prerequisite for the management of ground water resources system in an optimal manner. The amount of groundwater recharge depends upon the rate and duration of rainfall, as rainfall is the principal means for replenishment of moisture in the soil water system and recharge to ground water. This paper investigated the relationship between rainfalls and groundwater recharge within Ona River basin, southwest Nigeria, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Moreover, despite the dereference in climate and geology, groundwater recharge followed a positive trend as rainfall in the two study areas. This reiterates what was reported earlier on by Oke et al [19]. This study has also proven that decreasing rainfall contributes to decreasing groundwater recharge, as pointed out by other researchers [9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, despite the dereference in climate and geology, groundwater recharge followed a positive trend as rainfall in the two study areas. This reiterates what was reported earlier on by Oke et al [19]. This study has also proven that decreasing rainfall contributes to decreasing groundwater recharge, as pointed out by other researchers [9].…”
Section: Discussionsupporting
confidence: 92%
“…Debatably, groundwater recharge is positively related to rainfall as decreasing precipitation is said to contribute more to decreasing groundwater table levels [9,19]. Nevertheless, this may not be scientifically true altogether as other factors come into play and the relation between rainfall and natural groundwater recharge may not be linear.…”
Section: Background Informationmentioning
confidence: 99%
“…Ironically, residents of many Nigerian communities ravaged by flooding also lack access to potable water. For instance Adesogan [26] reported poor water supply coverage for nearly 22% across the South West region of Nigeria while Oke et al [27] noted there is a challenge of water sourcing within a major portion of this region. An integrated solution may be a rainwater harvesting system designed to meet water supply needs and also serving as an FRM scheme.…”
Section: Absence Of Integration Between Urban Development and Frmmentioning
confidence: 99%
“…The study also revealed that an inverse relationship was observed between annual average humidity and GW recharge, whereas there was a direct relationship between rainfall and annual GW recharge over the study period. From the rainfall-recharge relationship in this study, it can be mentioned that the amount of GW recharge highly relies on the rate and duration of rainfall, as rainfall is the principal means for replenishment of moisture in the soil water system and recharge to ground water (Oke et al, 2014).…”
Section: Variation In Annual Gw Recharge and Its Relationship With DImentioning
confidence: 99%